Data Cultures: a scoping literature review - Oliver, Gillian; Cranefield, Jocelyn; Lilley, Spencer; Lewellen, Matthew (Information Research an international electronic journal, 2023)
Introduction. This paper reports the outcomes from a literature review of the concept of data cultures as the first step in extending the body of knowledge relating to information culture in the information science domain and raising awareness of the need for further research. Method. A scoping literature review was conducted of English language peer reviewed publications indexed in SCOPUS as well as specialist information and computer science databases. Results. There is a rich and growing body of research concerned with the concept of data cultures, spread across a wide range of disciplines but without any evidence of a universally adopted shared definition or understanding. Information science expertise does not appear to be widely recognised as providing any essential insight into this problem space. Conclusion. The knowledge and understanding of information cultures gained from information science research does not seem to be being applied to data dominated environments. Expertise relating to information behaviour, digital literacies, information management, digital sustainability and preservation are unique and essential perspectives to understand issues relating to data cultures.